Broadband gap‐coupled half‐hexagonal microstrip antenna fed by microstrip‐line resonator. Issue 6 (25th February 2018) - Rathod, S. M.; Awale, R. N.; Ray, K. P.; Chaudhari, Amar D.
Abstract: Half‐hexagonal microstrip antenna (H‐HMSA) is a compact version of HMSA, as it resonates at the same fundamental mode frequency. In this article, a compact configuration of a single layer, broadband gap‐coupled H‐HMSA has been proposed. Gap‐coupled H‐HMSA is fed indirectly by a λ/2 microstrip‐line resonator. Broad bandwidth (BW) is achieved with an effective use of resonance introduced by λ/2 resonator and gap‐coupled half‐hexagonal radiating patches. A peak gain of 7.07 dBi and measured BW ( S 11 ≤ −10 dB) of 11.5% at the center frequency of 5.2 GHz have been achieved, which occupies a small volume of 0.023 λ0 3 including the ground plane. The radiation patterns remain in the broadside direction throughout the return loss BW. Simulated results of the proposed antenna configuration are experimentally validated with good agreement.